Ephemeroptera (Insecta) from Pernambuco State, northeastern Brazil - Lima,Lucas R. C. (2012)
The first list of the species of Ephemeroptera from Pernambuco State, Northeastern Brazil, is presented. The survey was based on collections from numerous rivers and streams of 17 counties. A total of five families, 28 genera, and 38 species were recorded, including 22 genera and 31 species newly recorded from Pernambuco State. Moreover, Farrodes tepui Domínguez, Molineri & Peters, 1996, Lisetta ernsti Thomas & Dominique, 2005, and Simothraulopsis (Maculognathus) sabalo Kluge, 2007 are recorded for the first time to Brazil.